The microstructure, composition, physical properties, and bioactivity of calcium silicate cement prototypes for vital pulp therapies - Vega Gonzalez, Marina; Espinosa Cristobal, Leon Francisco; Dominguez-Perez, Ruben Abraham; Higareda-Mendoza, Ana Edith; Dominguez-Perez, Ricardo; Sanchez-Lara y Tajonar, Roberto Gustavo (2024)
Hydraulic calcium silicate cements (HCSCs) are valuable for various dental procedures. However, several reports document inherent limitations and complaints about their high costs, hindering accessibility in low—and middle-income countries. This study aimed to characterize four low-cost HCSC prototypes to show their microstructure, composition, and fundamental physical properties. Four HCSC prototypes were formulated: 1- calcium silicate powder with 17.5 wt. % replacement of calcium tungstate, 2- calcium silicate powder with 17.5 wt. % replacement of zirconium oxide, 3- calcium silicate powder with 17.5 wt. % replacement of calcium tungstate and 2.5 wt. % of zirconium oxide and 4- calcium silicate powder with 10 wt. % replacement of calcium tungstate and 10 wt. % replacement of zirconium oxide. Scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction were used to assess their microstructure and composition. Additionally, radiopacity, setting time, solubility, pH, and in vitro bioactivity were evaluated at different time points and contrasted with controls (Mineral trioxide aggregate –MTA Angelus- and Intermediate restorative material -IRM-). Their production cost was significantly lower than commercially available HCSCs. All prototypes exhibited a microstructure and composition comparable to MTA Angelus. All the prototypes exhibited radiopacity exceeding 3 mm of aluminum and shorter initial and final setting times than MTA Angelus. The solubility of some prototypes closely adhered to the ISO standard recommendation of 3% after 1 day, and all promoted an alkaline pH and the formation of calcium/phosphate precipitates. These promising findings suggest the potential clinical application of these prototypes. However, further research is necessary to evaluate their mechanical and biological properties for definitive clinical use.